The sustainable city - Cohen, Steven, 1953 September 6- (Columbia University Press, 2018)
Living sustainably is not just about preserving the wilderness or keeping nature pristine. The transition to a green economy depends on cities. For the first time in human history, the majority of the people on the planet live in urban areas. If we are to avert climate catastrophe, we will need our cities to coexist with nature without destroying it. Many places are already investing in the infrastructure of the future-including renewable energy, energy efficiency, mass and personal transit, and advanced sewage and waste management-but the modern city still has a long way to go. In The Sustainable City, Steven Cohen provides a broad and engaging overview of the urban systems of the twenty-first century, surveying policies and projects already under way in cities around the world and pointing to more ways progress can be made. Cohen discusses the sustainable city from an organizational-management and public-policy perspective that emphasizes the local level, looking at case studies of existing legislation, programs, and public-private partnerships that strive to align modern urban life and sustainability. From waste management in Beijing to energy infrastructure in Africa to public space in Washington, D.C., there are concrete examples of what we can do right now. Cohen synthesizes the disparate strands of sustainable city planning in an approachable and applicable guide that highlights how these issues touch our lives on a daily basis, whether the transportation we take, where our energy comes from, or what becomes of our food waste.